A Review on the Geotechnical and Electrical Properties of Hydrocarbon-Contaminated Soils (University of Thi-Qar Journal for Engineering Sciences, 2025)
Oil contamination of the ground due to leaks in oil pipes, transportation of hydrocarbon products, or during excavation stages of oil production can alter the subsurface's physical characteristics, mechanical behavior, chemical reactivity, and electrical response. Consequently, the subsurface may become unsuitable for construction and might require significant remediation. Therefore, it is essential to gain a deep understanding of the overall attitude and the associated ground properties in case of pollution. This paper reviews the existing literature related to hydrocarbon soil contamination. The main focus is on previous studies that evaluate the geotechnical and electrical properties of subsoil after exposure to crude oil or its products. The paper emphasizes soil properties such as soil particles, Atterberg limits, specific gravity, compaction characteristics, pH value, undrained shear strength, and consolidation response. It is found that soil properties are significantly affected by contamination, depending on soil type, hydrocarbon product, and contamination proportions. Additionally, methods of soil treatment are briefly discussed.